2011
DOI: 10.1115/1.4004086
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mixing in a Simple Paddle Mixer Using Experimentally Derived Velocity Fields

Abstract: The flow field in a cylindrical container driven by a flat bladed impeller was investigated using Particle Image Velocimetry (PIV). Three Reynolds numbers (0.02, 8, 108) were investigated for different impeller locations within the cylinder. The results showed that vortices were formed at the tips of the blades and rotated with the blades. As the blades were placed closer to the wall the vortices interacted with the induced boundary layer on the wall to enhance both regions of vorticity. Finite Time Lyapuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In [5], the flow field in a cylindrical container driven by an impeller with flat blades was considered. The studies were performed using particle imaging velocimetry (PIV).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5], the flow field in a cylindrical container driven by an impeller with flat blades was considered. The studies were performed using particle imaging velocimetry (PIV).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of the analysis [1][2][3][4][5][6][7][8][9][10], it can be concluded that the reasonable choice of the material of the blades is not represented properly, which is especially important in the design of mixers. Mixer blades during operation are in a state of abrasive friction and their durability is determined by the quality of the alloy from which they are made.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing conditions affect the resistance of the blades, so the results of modeling during mixing of various media by the discrete element method (DEM) [2,3], Advanced DEM-CFD [4] or particle imaging velocimetry (PIV) [5] are of interest. In addition, it should be noted analytical methods for constructing blade profiles [6], which make it possible to determine rational parameters and geometric characteristics of the profile, which improve the quality of mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, WCSPH method, improved by using pressure velocity‐decoupling, advanced second‐order discretization, and shifting algorithm, is introduced and used to simulate the mixing phenomena in a cylindrical paddle mixer. Regardless of the scales at which the fluid mixing occurs, this kind of mixer has widely been investigated by using experimental and numerical methods . The stirred vessels have also widely been investigated .…”
Section: Introductionmentioning
confidence: 99%